Organizações sociais de saúde: análise dos contratos de gestão e termos aditivos do estado de São Paulo - Castro, Gabriella Bigossi de (2019)
Using the State ́s inability to take care of the demands directed to it as a justification and as a form of criticism to its rigid, inefficient and bureaucratic public administration, the State ́s reform of its public administration system has proposed the process of transferring the execution of services that are not exclusive to the State over to Social Organizations. In spite of limited empirical evidence regarding Social Organizations for Health (OSS), not only do these organizations continue to make headway managing Brazil ́s Public Health System (Sistema Único de Saúde – SUS) but they have also received large amounts of public resources to do so. According to Article 16 of Law 4.320, from 1964, economical advantage must be proven before a Third Sector organization receives public funding. The large number of Additive Terms (AT) to the Management Contracts (MC) that have been identified in the state of São Paulo (SP), which pioneered OSS management, has resulted in a need to investigate the content of these documents regarding both the forwarding of financial resources and the services which are offered. It is possible that the large number of AT may increase the amount of public resources forward to OSS. Considering the history of the private sector ́s interest in the Public Health System, this forwarding of resources might motivate the OSS to seek partnerships with the State more than a mere interest in the effectiveness of the Public Health System management. Having the Health planning as proposed in the MC and AT established between 2013 and 2017 as the object of its study, this research seeks to analyze the dynamic of resource forwarding and care goals stipulated in SP. This study is exploratory and descriptive in nature, with quantitative and qualitative approaches. A total of 27 OSS were identified in the management of 98 health establishments. The total amount of forwarded to the management of 89 establishments exceeded the amount stipulated in the MC by 6.23%; however, there was an average increase of 20.22% in the transfer to 20 establishments. The most valuable service was Medical Appointments. Neither qualitative nor quantitative goals were not met by OSS. More health services were excluded than included and most care goals were reduced, especially regarding Emergency Hospital Services and Ambulatory Dental Services. The price of the four main services offered showed, when considered together, an average increase of 22.82%. These partnerships seem to bring more benefits to the OSS, since the forwarding of resources increase on a constant basis while health services offered to the population decrease, which shows the need for further investigation